Perceptions of Students from the Physical Education, Health, and Recreation Program at Riau University Participating in the 2022 Teaching Assistance Program Implementation - Chandra Gultom, Yoel; Prima Aspa, Agus; Hidayat, Hirja (Jurnal Pendidikan Jasmani (JPJ), 2024)
This research aims to understand the perceptions of students in the Physical Education, Health, and Recreation Study Program at Riau University regarding the implementation of the Teaching Assistance program in 2022. The research problem includes discrepancies and a lack of socialization concerning the program's implementation. The study employs a qualitative design with a descriptive approach. The research population consists of 11 students from the Physical Education, Health, and Recreation program at UNRI and their supervising teachers. Purposive sampling was used to select participants, and data was collected through semi-structured interviews, documentation, and literature review. Data analysis followed the interactive model of Miles and Huberman, involving data reduction, data presentation, and conclusion drawing. Triangulation was employed to ensure data validity. The findings indicate that students are not fully prepared to implement the Teaching Assistance program due to insufficient preparation and being in the early stages of their studies. Additionally, the lack of understanding and socialization of the program, along with the irrelevance of the credit conversion, presents further challenges. In conclusion, students' readiness is insufficient, and the credit conversion issue is significant. Future research should focus on improving the socialization process and refining the program specifications in line with established guidelines.